2017
DOI: 10.1080/03019233.2017.1305676
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of macro-inclusions in low carbon aluminium-killed steel slabs

Abstract: Macro-inclusions in low carbon, aluminium-killed steel slabs were characterised by step-machining within a 10 mm zone from the slab surface using an ASPEX automatic inclusion analyzer. Dendritic structures within the cross-section of slabs were examined. The results show that alumina clusters and alumina associated with bubbles are the dominant macro-inclusions. Along the slab width direction, macro-inclusions were mostly found at the slab centre because of the deeper hooks and freezing meniscus surrounding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
(51 reference statements)
1
8
0
Order By: Relevance
“…Figure 11 also shows that with increasing casting speed, the inclusion particle entrapment probability decreased. The aforementioned conclusions were consistent with the statistical conclusions concerning slab cleanliness presented in References [27][28][29]. When the shell moved downwards, the molten steel at the meniscus overflowed out of the shell, leading to particles gathering near the meniscus being deposited above the nascent hook.…”
Section: Inclusions Entrapped By Hookssupporting
confidence: 89%
See 1 more Smart Citation
“…Figure 11 also shows that with increasing casting speed, the inclusion particle entrapment probability decreased. The aforementioned conclusions were consistent with the statistical conclusions concerning slab cleanliness presented in References [27][28][29]. When the shell moved downwards, the molten steel at the meniscus overflowed out of the shell, leading to particles gathering near the meniscus being deposited above the nascent hook.…”
Section: Inclusions Entrapped By Hookssupporting
confidence: 89%
“…Shorter and thinner hooks were formed after the continuous casting process was optimized by using a higher casting speed or pouring temperature or higher crystalline tendency of the mold flux (mech-I of OM formation) to suppress the solidification of the meniscus or by using a mold flux with low viscosity and solidification temperature (mech-II and mech-III) to enhance the lubrication for infiltration of the mold flux and reduce the slag rim size [26]. Previous studies have confirmed that the entrapment of inclusions by hooks results in more macro-inclusions being present at the subsurface than in the slab interior [27][28][29]. To the best of our knowledge, however, a study on the specific process of hook inclusion entrapment has not yet been published.…”
Section: Introductionmentioning
confidence: 99%
“…Over 50% of the total oxygen is removed between the tundish and the cast slabs although the total oxygen at different width locations in the slabs is essentially the same. Deng et al 18 found variations in the number of largesized inclusions at different width locations, perhaps because the total oxygen content generally represents the amount of small inclusions distributed throughout the steel and only occasionally includes some large inclusions.…”
Section: Total Oxygen and Nitrogen Contentsmentioning
confidence: 99%
“…However, in the present work, a substantial difference in inclusion size and number density was found between the samples taken from the tundish and the final slabs. In the current study, the evolution of macro inclusions during continuous casting was elucidated by means of total oxygen measurements, large-area inclusion characterisation using ASPEX [18][19][20] and analysis of nozzle blockage deposits. Based on the findings from this investigation, formation mechanisms for the different macro inclusions found in the slabs are proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The solubility of magnesium in molten steel is relatively high. Magnesium has a strong affinity with oxygen and sulfur, which can effectively reduce the content of O and S in steel, and improve the quantity and morphology of inclusions in steel; moreover, it has an obvious modification effect on oxide inclusions and plays a role in purifying molten steel [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%